Diagnosis and management of primary central nervous system lymphoma: a consensus practice statement from the Australasian Lymphoma Alliance. Issue 9 (27th July 2022) - Keane, Colm; Hamad, Nada; Barraclough, Allison; Lee, Yoo Y.; Talaulikar, Dipti; Ku, Matthew; Wight, Joel; Tatarczuch, Maciej; Swain, Fiona; Gregory, Gareth P.
Abstract: Primary central nervous system lymphoma is a clinicopathological disease entity that accounts for 1% of all non‐Hodgkin lymphoma (NHL). Advanced patient age, adverse disease biology and complexities of diagnosis and treatment render outcomes markedly inferior to systemic NHL. Despite this, an increasing evidence base, including limited randomised controlled clinical trial data, is informing optimal therapeutic strategies with methotrexate‐based induction chemotherapy schedules and intensified consolidation in selected patients. This practice statement represents an evidence‐based review of the literature and has been devised to assist healthcare professionals in the diagnosis and management of this disease.